Possible effects of inhibition of IKr and IKs on field-potential waveforms in the human iPS cell-derived cardiomyocytes sheet - Junko Matsuo; Yuji Nakamura; Hiroko Izumi-Nakaseko; Kentaro Ando; Yuko Sekino; Atsushi Sugiyama (Elsevier, 2015)
In order to investigate how IKr and IKs inhibitions affect waveforms of the field potential in the human iPS cell-derived cardiomyocytes sheet, we analyzed the effects of E-4031 and chromanol 293B on the maximum upslope and peak amplitude of its second wave (n = 7 for each drug). E-4031 in 10-100 nM as well as chromanol 293B in 3-30 μM prolonged the field-potential duration, whereas E-4031 decreased the upslope in 10-100 nM and amplitude at 100 nM, which was not observed by chromanol 293B. Thus, the decrease of the upslope can be used as a supplemental marker of drug-induced IKr inhibition.